Progression Analysis of Ossification and Bone Metabolism in Patients with Cervical Ossification of the Posterior Longitudinal Ligament - Yamazaki, Akiyoshi; Kawashima, Hiroyuki; Ohashi, Masayuki; Sato, Masayuki; Katsumi, Keiichi; Mizouchi, Tatsuki; Watanabe, Kei; Hirano, Toru; Ishikawa, Yuya; Izumi, Tomohiro (Journal of Spine Research, 2021)
Introduction: In the previous study, we established a method for three-dimensional analysis of computed tomography (CT) of cervical ossification of the posterior longitudinal ligament (OPLL) to identify the risk factors for the progression of ossification. The aim of this study was to establish biomarkers predicting progression of ossification by considering bone metabolism.Methods: In this study, 44 OPLL patients, who underwent imaging examinations and bone metabolism tests in our hospital or related facilities, were included. The subjects consisted of 26 men and 18 women with the mean age of 61 years.Bone metabolism was measured using complete blood count, biochemical parameters, electrolyte, 25-hydroxyvitamin D (25OHD), intact parathyroid hormone (PTH), fibroblast growth factor 23 (FGF-23), procollagen type 1 amino-terminal propeptide (P1NP), tartrate-resistant acid phosphatase 5b (TRACP-5b), sclerostin and Dickkopf-related protein 1 (Dkk-1), and bone mineral density. Progression of ossification was measured using the three-dimensional analysis of the volume of ossification to calculate the annual rate of increase. Based on the previous findings of the annual rate of increase (7.5%/year) in patients with cervical OPLL after laminoplasty, in the present study, the progression group (P group) was defined as those with an annual rate of increase of ≥8%, whereas the nonprogression group (N group) was defined as those with an annual rate of increase of <8%. Univariate and multivariate analyses were used to identify related factors.Results: The mean annual rate of increase was 5.0% per year. Univariate analysis identified age (P group, 50.0 years; N group, 63.9 years), BMI (P group, 30.4 kg/m2; N group, 24.8 kg/m2), serum phosphorus level (P group, 2.7 mg/dL; N group, 3.1 mg/dL), and TRACP-5b level (P group, 303.6 mU/dL; N group, 468.3 mU/dL) as significant factors (all, p < 0.05), whereas multivariate analysis identified age as the only significant factor (p < 0.05).Conclusions: In our previous studies, younger age and obesity were identified as significant risk factors for progression of ossification. Hence, the present study's results are consistent with our previous findings. In addition, univariate analysis also identified serum phosphorus and TRACP-5b as related factors. Both factors are closely related to bone metabolism and easy to measure. Future studies are required to evaluate the factors as possible biomarkers for the progression of OPLL ossification.